Draft Annual Plan 2008-2009 Orissa Volume-II - Planning Commission (Planning Commission, 2008)
GN Statement-A (Abstract to Annexure-I) , GN Statement-B (Proposed Outlays from State Budget, State PSU and Local Bodies) , GN Statement-C (Proposed Outlays from Rural and Urban Local Bodies , Proposed Outlays , Physical Targets and Achievements , Externally Aided Projects , Bharat Nirman Programmes , Centrally Sponsored Schemes , Tribal Sub-Plan (TSP) -I - Financial outlays , Tribal Sub-Plan (TSP) - Il Physical Targets and Achievements.
Government of Orissa, Planning and Co-ordination Department
Government of Orissa